CSR's Measuring Corporate Social Responsibility Practice in Islamic Banking: A Review - Abdullah Rajeh Ali Alamer; Hussin Bin Salamon; Muhammad Imran Qureshi; Amran Md. Rasli (International Journal of Economics and Financial Issues, 2015)
Academic efforts have started for around one decade to measure corporate social responsibility (CSR) in Islamic Banks (IBs) practices. The authors, in this field, have written based on two thoughts wide and narrow of the CSR in Islamic banking but there still are important gaps that need to fill. The first authors were dependent who established variety indexes and the second group was independent writers who followed benchmark index to measure of CSR in Islamic banking. This work tried to compare between the current literatures reviews of CSR in IBs and the current criticisms of social impacts on the society from Islamic banking operations. In Islam, business processes of IBs can never be separated from the ethical considerations of society. These considerations of the IBs for the society can be as new dimensions of CSR to measure the real impacts. This article shaped new contribution in the CSR in IBs' operations to open the door to more researches to arrive the deeper understanding and clarification. Keywords: Corporate Social Responsibility, Islamic Banks, Business Processes JEL Classifications: G30